2013
DOI: 10.1089/jmf.2012.0303
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Virgin Coconut Oil and Its Medium-Chain Fatty Acids onClostridium difficile

Abstract: Clostridium difficile is the leading cause of hospital-acquired antibiotic-associated diarrhea worldwide; in addition, the proliferation of antibiotic-resistant C. difficile is becoming a significant problem. Virgin coconut oil (VCO) has been shown previously to have the antimicrobial activity. This study evaluates the lipid components of VCO for the control of C. difficile. VCO and its most active individual fatty acids were tested to evaluate their antimicrobial effect on C. difficile in vitro. The data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 29 publications
5
77
0
2
Order By: Relevance
“…Another study investigated the effect of virgin coconut oil on toxin A‐ and toxin B‐positive C. difficile (ATCC 9689) in vitro (Shilling et al . ). Virgin coconut oil did not show any inhibitory effect against this C. difficile strain, however, when the coconut oil was digested with porcine lipase, the resulting product inhibited 99·9% of overnight growth of C. difficile at concentration of 1·2% v/v (Shilling et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study investigated the effect of virgin coconut oil on toxin A‐ and toxin B‐positive C. difficile (ATCC 9689) in vitro (Shilling et al . ). Virgin coconut oil did not show any inhibitory effect against this C. difficile strain, however, when the coconut oil was digested with porcine lipase, the resulting product inhibited 99·9% of overnight growth of C. difficile at concentration of 1·2% v/v (Shilling et al .…”
Section: Discussionmentioning
confidence: 97%
“…Another study investigated the effect of virgin coconut oil on toxin A-and toxin B-positive C. difficile (ATCC 9689) in vitro (Shilling et al 2013). Virgin coconut oil did not show any inhibitory effect against this C. difficile strain, however, when the coconut oil was digested with porcine lipase, the resulting product inhibited 99Á9% of overnight growth of C. difficile at concentration of 1Á2% v/v (Shilling et al 2013). These findings correlated with the results from our study, as no antimicrobial activity was observed for undigested virgin coconut oil against any of tested micro-organisms using either agar well diffusion or broth microdilution techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Yuniwarti et al [70] investigated the effect of VCO on lymphocyte and CD4 (cluster of differentiating), a surface protein on T lymphocyte, in chicken which had been vaccinated against the avian influenza virus. The study which applied the completely randomised factorial design method concluded that fatty acids of VCO were able to boost the amount of lymphocyte and CD4 on vaccinated or unvaccinated broiler chicken showing that VCO was potentially acting as an immunomodulator which therefore could increase chicken immunity and in combating a viral infection.…”
Section: F Antiviral Action Of Coconut Oilmentioning
confidence: 99%
“…Certain medium-chain fatty acids, such as lauric acid derived from virgin coconut oil, caused a significant inhibition of C. difficile growth in an in vitro study [130]. It is postulated that bacterial cell death is caused by the incorporation of these fatty acids in the bacterial cell membrane that brings forth a substantial change in its permeability as well as by a probable interference with cellular metabolism [131].…”
Section: Antibiotics and Non-antibiotic Anticlostridial Agentsmentioning
confidence: 99%